Analisis Kritis Gerakan Nasional Budaya Sensor Mandiri dengan Perspektif Deontologi Immanuel Kant - Prabowo, Hadi; Azwar, Azwar; Kuswanti, Ana (Dinasti Research, 2026)
Launched in 2021 by Indonesia's Film Censorship Board (LSF), the National Self-Censorship Culture Movement (GNBSM) aims to encourage ordinary citizens to make mindful choices about film content, drawing on personal moral judgment alongside existing regulations. This paper thoughtfully explores how Immanuel Kant's enduring ideas on duty especially the categorical imperative and individual autonomy help us understand both the high ideals driving GNBSM and the everyday hurdles in making them work amid streaming platforms and digital viewing habits. Through close reading of three LSF studies from 2022-2024 that captured perspectives from over 2,000 people across Indonesia, we notice some striking patterns: nearly everyone (92.97%) sees the value in age ratings, yet far fewer (just 45%) feel the campaign's message truly lands with them; rules cover only a sliver (5.17%) of where films are actually watched, since most viewing (94.83%) happens online; and grasp of these ideas differs sharply by education, with higher-educated groups at 60-70% buy-in versus 30-40% elsewhere. What's particularly telling is this tension: 81% now skip unsuitable material, but Kant would argue real moral agency needs deeper reasoning, not just habit. Looking ahead with care for all sides, the paper suggests practical shifts retelling the story through Kant's lens for better connection, extending efforts to where people really watch films, fostering community discussions on ethics, and creating spaces for genuine dialogue. In essence, Kant reminds us that true ethical progress happens when principles resonate in both action and understanding.